2020
DOI: 10.1002/cam4.2932
|View full text |Cite
|
Sign up to set email alerts
|

Novel risk group stratification for metastatic urothelial cancer patients treated with immune checkpoint inhibitors

Abstract: Background: We developed a novel risk scoring system for urothelial cancer (UC) patients receiving immune checkpoint inhibitors (ICI). Methods: We conducted a retrospective review of 67 UC patients treated with ICI at Winship Cancer Institute of Emory University from 2015 to 2018. Using stepwise variable selection in Cox proportional hazard model and Sullivan's weighting schema, baseline platelet-to-lymphocyte ratio (PLR), presence of liver metastasis, baseline albumin, and baseline Eastern Cooperative Oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…A risk scoring using baseline platelet-to-lymphocyte ratio, presence of liver metastasis, albumin, and ECOG PS has been developed on a cohort of 67 UC patients treated with ICIs. 28 A three-factor model including genomic (namely, a single-nucleotide variant count >9) and clinical (i.e. NLR <5 and lack of visceral metastasis) variables was related to benefit from ICI but not from taxane therapy in 62 patients with metastatic UC.…”
Section: Discussionmentioning
confidence: 94%
“…A risk scoring using baseline platelet-to-lymphocyte ratio, presence of liver metastasis, albumin, and ECOG PS has been developed on a cohort of 67 UC patients treated with ICIs. 28 A three-factor model including genomic (namely, a single-nucleotide variant count >9) and clinical (i.e. NLR <5 and lack of visceral metastasis) variables was related to benefit from ICI but not from taxane therapy in 62 patients with metastatic UC.…”
Section: Discussionmentioning
confidence: 94%
“…Sonpavde et al (2016) ultimately improved the concordance statistic of their model incorporating ECOG PS, hemoglobin, liver metastasis, and TFPC from 0.616 to 0.646 by adding low albumin, a known marker of inflammation, as a fifth and final factor in their prognostic classification of patients receiving chemotherapy in the salvage setting [39]. While investigating the factors most predictive of clinical outcomes in patients with metastatic UC treated with ICI, our own group developed the Emory Risk Scoring System that associates increased baseline platelet‐lymphocyte ratio, low baseline albumin, metastasis to the liver, and higher ECOG PS with decreased survival [11]. Associating elevated levels of systemic inflammation through a variety of biomarker proxies with prognosis is a path often traveled, as evidenced above.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation alone and in combination with other clinical factors has been shown to predict poorer response to ICI across genitourinary cancers including UC [8][9][10][11][12][13][14]. C-reactive protein (CRP) is an acute phase reactant that increases in response to proinflammatory cytokines such as interleukin (IL)-6 and IL-1β and has negative prognostic value across multiple malignancies and stages [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Shabto et al reported a novel risk stratification system for urothelial carcinoma patients treated with ICI using platelet-to-lymphocyte risk as an inflammatory marker in addition to Eastern Cooperative Oncology performance status (ECOG PS), presence of liver metastasis, and albumin [ 37 ].High PLR was seen to be demonstrating shorter PFS and OS compared to patients with low PLR with NSCLC treated with atezolizumab [ 28 ]. Higher PLR of >168.13 before the fifth dose of ICIs was noted to be a prognostic marker and correlated with smaller OS in patients with NSCLC receiving nivolumab and durvalumab [ 38 ].…”
Section: Platelet-to-lymphocyte Ratio (Plr)mentioning
confidence: 99%